The role of the calmodulin‐binding and calmodulin‐like domains of the epidermal growth factor receptor in tyrosine kinase activation. Issue 7 (10th December 2020) - Abdelli, Faten; Jellali, Karim; Anguita, Estefanía; González‐Muñoz, María; Villalobo, Eduardo; Madroñal, Ivan; Alcalde, Juan; Ben Ali, Mamdouh; Elloumi‐Mseddi, Jihene; Jemel, Ikram; Tebar, Francesc; Enrich, Carlos; et al.
Abstract: The epidermal growth factor receptor (EGFR) harbors a calmodulin (CaM)‐binding domain (CaM‐BD) and a CaM‐like domain (CaM‐LD) upstream and downstream, respectively, of the tyrosine kinase (TK) domain. We demonstrate in this paper that deletion of the positively charged CaM‐BD (EGFR/CaM‐BD∆) inactivated the TK activity of the receptor. Moreover, deletion of the negatively charged CaM‐LD (EGFR/CaM‐LD∆), leaving a single negative residue (glutamate), reduced the activity of the receptor. In contrast, substituting the CaM‐LD with a histidine/valine‐rich peptide (EGFR/InvCaM‐LD) caused full inactivation. We also demonstrated using confocal microscopy and flow cytometry that the chimera EGFR‐green fluorescent protein (GFP)/CaM‐BD∆, the EGFR/CaM‐LD∆, and EGFR/InvCaM‐LD mutants all bind tetramethylrhodamine‐labelled EGF. These EGFR mutants were localized at the plasma membrane as the wild‐type receptor does. However, only the EGFR/CaM‐LD∆ and EGFR/InvCaM‐LD mutants appear to undergo ligand‐dependent internalization, while the EGFR‐GFP/CaM‐BD∆ mutant seems to be deficient in this regard. The obtained results and in silico modelling studies of the asymmetric structure of the EGFR kinase dimer support a role of a CaM‐BD/CaM‐LD electrostatic interaction in the allosteric activation of the EGFR TK. Abstract : Model of the asymmetric structure of the epidermal growth factor receptor kinase dimer showing that the calmodulin‐binding domain (blue surface) and calmodulin‐like domain (red surface) of apposed monomers are well positioned to establish electrostatic interaction. The model highlights the transmembrane‐juxtamembrane segments and the activator and receiver monomers in relaxed and activated states.